2003
DOI: 10.1152/ajpendo.00079.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the portal signal in a nonsteady hyperglycemic state in conscious dogs

Abstract: . Characterization of the portal signal in a nonsteady hyperglycemic state in conscious dogs. Am J Physiol Endocrinol Metab 284: E148-E155, 2003. First published September 11, 2002 10.1152/ajpendo.00079.2002To characterize the "portal signal" in a nonsteady hyperglycemic state, the kinetic relationship between net hepatic glucose balance (NHGB) and either hepatic glucose load (HGL) or plasma insulin level was determined during glucose infusion using a catheter technique in 36 conscious dogs. Glucose was infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(19 reference statements)
2
7
0
Order By: Relevance
“…4) was similar to that achieved between NHGU and HGL in dogs (28). The slope of the regression lines of the net hepatic glycogen against the HGL axis was two times higher in Po than in Pe in rats, whereas that of NHGU was four times higher than Pe in dogs, with the intercepts on the HGL axis converging near the basal values in both animals.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…4) was similar to that achieved between NHGU and HGL in dogs (28). The slope of the regression lines of the net hepatic glycogen against the HGL axis was two times higher in Po than in Pe in rats, whereas that of NHGU was four times higher than Pe in dogs, with the intercepts on the HGL axis converging near the basal values in both animals.…”
Section: Discussionsupporting
confidence: 80%
“…This difference may be attributed, at least in part, to the difference in the experimental conditions. The A-P gradients were linearly related not only to hepatic glycogen synthesis in this study but also to NHGU in the previous study in dogs (28), whereas NHGU was saturated with increasing A-P gradients at greater than ϳ1 mmol in their study. The 80% replacement of Po by Pe achieved a comparable reduction in the A-P gradients in our study, whereas it evoked a lesser reduction in the A-P gradients in their study (31).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous reports suggested that some glucose sensors that can rapidly detect changes in glucose concentration are present in the brain (6,37,49), pancreatic islets (21,45), gut (45), and hepatoportal region (8,34,35). Recently, it has been demonstrated that postprandial secretion of glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) could induce an early insulin response.…”
mentioning
confidence: 99%
“…It has been suggested that glucose sensors representing the hepatoportal region detect a glucose gradient between the portal vein and arterial blood (16,17,23) and stimulate glucose utilization and glycogen storage in the liver (34,35) during glucose perfusion into the portal vein, and that these responses are mediated by autonomic nerves. Guarino et al (20) also suggested that parasympathetic nerves in the liver control peripheral insulin sensitivity via an NO-dependent pathway.…”
mentioning
confidence: 99%